2017
DOI: 10.1111/rec.12650
|View full text |Cite
|
Sign up to set email alerts
|

Sheep trampling on surface‐lying seeds improves seedling recruitment in open sand ecosystems

Abstract: Low‐intensity grazing with domestic ungulates is an important tool in restoration to enhance habitat openness and foster light‐demanding plant species. Ungulates affect plant regeneration in different ways; one important factor is trampling. We hypothesized that in dry open sand ecosystems sheep trampling is beneficial for seedling recruitment. Therefore, we set up a standardized laboratory experiment, where we simulated trampling on surface‐lying seeds and measured the number of seedlings, mean germination ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 70 publications
(109 reference statements)
2
22
0
Order By: Relevance
“…Red deer have been shown to disperse high numbers of plant species, especially early-successional (Iravani et al, 2011) as well as rare and endangered species (Wichelhaus, 2017). In addition, we might assume that red deer enhance plant diversity by trampling, which can create gaps and improve the microclimatic conditions for seedling emergence, as has been demonstrated for the hoof imprints of sheep or cattle (Ludvíková et al, 2014;Eichberg & Donath, 2018).…”
Section: Red Deer Exclusion Effects In Grasslandsmentioning
confidence: 99%
“…Red deer have been shown to disperse high numbers of plant species, especially early-successional (Iravani et al, 2011) as well as rare and endangered species (Wichelhaus, 2017). In addition, we might assume that red deer enhance plant diversity by trampling, which can create gaps and improve the microclimatic conditions for seedling emergence, as has been demonstrated for the hoof imprints of sheep or cattle (Ludvíková et al, 2014;Eichberg & Donath, 2018).…”
Section: Red Deer Exclusion Effects In Grasslandsmentioning
confidence: 99%
“…Fischer et al ; Opperman & Merenlender ; Yates et al ; Kiehl & Pfadenhauer ) as it can limit competition, favor some species, and introduce new species. Eichberg and Donath () studied the effects of simulated trampling by artificial sheep hooves on germination and seedling recruitment of plant species from dry sandy grasslands and of ruderals in a laboratory experiment. They showed that trampling pressed seeds into the upper soil layers and strongly promoted seedling emergence due to positive effects on microclimate.…”
Section: Improvement Of Establishment Successmentioning
confidence: 99%
“…In most cases, decreased management intensity will cause an increase in abundance and number of potentially dominant competitors of the subjected grassland community. During restoration planning, postrestoration management should be carefully selected because cessation or improper management can strongly threaten restoration success (Kelemen et al ; Eichberg & Donath ). Successful management of restored sites creates favorable light conditions, ensures the presence of gaps needed for the regeneration of target species, and provides control of potentially dominant native and non‐native nontarget species (Tischew et al ).…”
Section: Long‐term Persistence Sustainability and Managementmentioning
confidence: 99%
“…Grazing by large herbivores is a major driver of the ecosystem processes in open landscapes worldwide (Metera, Sakowski, Słoniewski, & Romanowicz, 2010;Leiber-Sauheitl et al, 2015;Rupprecht, Gilhaus, & Hölzel, 2016). Grazing animals shape species composition through the consumption of biomass, redistribution of nutrients via deposition of dung and urine (Gillet, Kohler, Vandenberghe, & Buttler, 2010;Ma et al, 2016), soil compaction and erosion via trampling (Eichberg & Donath, 2018), and dispersal of seeds on their fur, hooves or via their dung (Couvreur, Verheyen, & Hermy, 2005;Will & Tackenberg, 2008;Freund, Carillo, Storm, & Schwabe, 2015). Via these mechanisms, grazers alter habitat conditions and create micro-habitats for plant species (Smit & Putman, 2011;Deák et al, 2017).…”
Section: Introductionmentioning
confidence: 99%